Economic values of some important traits for smallholder dairy production in Central Ethiopia - Hunde, Direba; Tadesse, Yosef; Tadesse, Million; Biratu, Kasa; Shumiye, Molla; Yadesa, Endale; Wedajo, Fikadu; Getahun, Kefale; Beneberu, Nibo; Gelmesa, Ulfina; Getachew, Tesfaye (Springer (part of Springer Nature), 2024)
Economic value (EV), sensitivity of EV and relative economic importance of milk yield (MY), age at first calving (AFC), calving interval (CI) and herd life (HL) traits were estimated for smallholder dairy cattle production in the central part of Ethiopia. The data on biological and economic parameters were collected using household interview and group discussions methods participating 238 farmers who had crossbred dairy cattle. Bio-economic model was used to calculate EV, sensitivity of EV and relative importance of EV. Cost of animal feed takes the highest share which accounted 81.35% of the total expenditure. The overall average profit per farmer expressed in Ethiopia currency (ETB, 1 US-$ = 39.55696 ETB) was 72,458.10 ± 5068 per year. Profitability of crossbred dairy cattle significantly varied (P < 0.05) between zones. Economic value estimated for MY, AFC, CI and HL in ETB were 13.38/kg, -16.19/day, -33.58/day and 79.55/day. The associated EV per additive standard deviation were 6083.62, -1311.59, -1271.05 and 117.73 ETB for MY, AFC, CI and HL, respectively. Analysis of sensitivity to scenario change (± 20%) showed that milk price had positive association with profit and EV, whereas feed price has inversely influenced both profit and EV. The profit obtained by farmers was altered by ± 29.08% and ± 12.31% as milk price and feed price fluctuated by ± 20%, respectively. Similarly, the EV of MY was changed by ± 20% with change in milk price and ± 7% with feed price. Scenario change in feed price (± 20%) has also caused ± 13.63% change on EV for AFC and ± 17.58% for CI. It can be noted that profit and EV of the traits were less sensitive to the change in price of milk, feed and labor. In general, the results of EV and profitability were encouraging for dairy farmers and the estimates can be used as an input for development of breeding program in the study area.